Implementasi Program Mahasiswa Wirausaha (PMW) Dalam Mewujudkan Mahasiswa Enterpreneur ( Studi Pada Universitas Brawijaya Malang) - Evi Ratnasari (Jurnal Administrasi Publik, 2013)
Abstract: The Implementation of Enterpreneurial Program (SEP) in Creating Student Enterpreneur. Based on the result findings of the study, it can be concluded that the implementation of Student Entrepreneurship Program (SEP) at UB in realizing Students Entrepreneur has been done pretty well. During the implementation process, the factors that support and hinder SEP are: (1) the implementation procedures run easily and smoothly, (2) there are 98 student out of 227 applicants are funded, (3) there are32 students out of 98 qualified students are funded by state funds and 66 students by BOPTN,(4) the elected students will get entrepreneurial training, (5) the supporting factor aregood funding, support from UB leaders, as well as the spirit of the students. (6) Factors that become theÂ  barrier is lack of monitoring and evaluation from the committee as well as the commitment of the students and sometimes slow funding, (7) SEP impact can reduce unemployment, students are more confident, willing to take risks, have the student leadership and more creative. Last but not least, the Student Entrepreneurial Program (SEP) at UB should give strict penalty for students who brake the rules, conducting regular entrepreneurial activity in every 3 years instead of once a year, establishingfinancial team to monitor the students and the further establishment of cooperation withsuccessful entrepreneurs beyond the campus for sharing, mainlyfor those who join the Student Entrepreneurial Program (SEP). Keywords: enterpreneur Â  Abstrak Abstrak: Implementasi Program Mahasiswa Wirausaha (PMW) dalam Mewujudkan Mahasiswa Enterpreneur. Berdasarkan hasil penelitian, dapat disimpulkan bahwa Implementasi Program Mahasiswa Wirausaha (PMW) di Universitas Brawijaya dalam mewujudkan mahasiswa Enterpreneur telah terlaksana dengan cukup baik. Dalam proses implementasinya, faktor yang mendukung dan menghambat serta dampak PMW tersebut, antara lain: (1) Prosedur pelaksanaannya berjalan dengan mudah dan lancar, (2) Dari 227 pendaftar ada 98 mahasiswa yang dibiayai, (3) Dari 98 mahasiswa ada 32 mahasiswa lolos didanai dana APBN dan 66 mahasiswa didanai dana BOPTN, (4) Mahasiswa yang terpilih mendapatkan pembekalan jiwa kewirausahaan, (5) Faktor yang menjadi pendukung adalah dana yang lancar, dukungan dari pimpinan-pimpinan UB, serta semangat mahasiswa. (6) Faktor yang menjadi penghambat adalah kurangnya tenaga monev dari panitia, lemahnya komitmen mahasiswa, dan dana yang kadang terlambat, (7) Dampak PMW bisa mengurangi pengangguran bagi yang sudah lulus, mahasiswa lebih percaya diri, berani mengambil resiko, memiliki jiwa kepemimpinan dan mahasiswa lebih kreatif.Saran untuk Program Mahasiswa Wirausaha (PMW) di Universitas Brawijaya Malang yaitu diberikannya sanksi yang tegas bagi mahasiswa yang melanggar, perlu diadakan kegiatan pembekalan kewirausahaan 3 tahun sekali bukan setahun sekali, tim monev lebih disempurnakan untuk memantau mahasiswa, dan perlu kerja sama para usahawan dari luar kampus yang sukses untukmenjadi tempat Sharing bagi mahasiswa yang mengikuti Program Mahasiswa Wirausaha (PMW). Kata kunci : enterpreneur